2004
DOI: 10.4049/jimmunol.172.4.2629
|View full text |Cite
|
Sign up to set email alerts
|

Role of Toll-Like Receptor 4 in Endotoxin-Induced Acute Renal Failure

Abstract: Toll-like receptor 4 (TLR4) is present on monocytes and other cell types, and mediates inflammatory events such as the release of TNF after exposure to LPS. C3H/HeJ mice are resistant to LPS-induced mortality, due to a naturally occurring mutation in TLR4. We therefore hypothesized that LPS-induced acute renal failure (ARF) requires systemic TNF release triggered by LPS acting on extrarenal TLR4. We injected C3H/HeJ mice and C3H/HeOuJ controls with 0.25 mg of LPS, and sacrificed them 6 h later for analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
186
2
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(206 citation statements)
references
References 37 publications
13
186
2
4
Order By: Relevance
“…PMN and their infiltration into the kidney have been proposed to cause renal dysfunction during sepsis (31)(32)(33). Our data provide additional experimental evidence for this concept of PMN-dependent organ failure during endotoxemia.…”
Section: Discussionsupporting
confidence: 58%
“…PMN and their infiltration into the kidney have been proposed to cause renal dysfunction during sepsis (31)(32)(33). Our data provide additional experimental evidence for this concept of PMN-dependent organ failure during endotoxemia.…”
Section: Discussionsupporting
confidence: 58%
“…In addition, previous research has shown a marked increase in TLR2 and TLR4 expression in renal tubular cells and in renal infiltrating cells caused by ischemia and reperfusion injury compared with control group (Kim et al, 2005;Pedregosa et al, 2011). Cunningham et al (2004) reported that TLR4 expression in the kidneys was critical in mediating LPS-induced acute kidney failure via proinflammatory cytokine release and subsequent kidney damage. Those results indicate that TLR4 mRNA expression levels in the kidneys may be caused by renal tubular cells or renal infiltrating cells damage, or LPS induction under AHS.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the role of TLR4 in infection-related acute renal failure has not been firmly established. Although endotoxin-induced acute renal failure was shown to be completely dependent upon extrarenal TLR4, 16 acute renal failure in the cecal ligation and puncture model of polymicrobial sepsis was independent of TLR4 signaling. 44 Second, it is clear from the present studies that TLR4 is pivotal in initiating the intrarenal inflammatory response that occurs in cisplatin nephrotoxicity.…”
Section: Discussionmentioning
confidence: 96%
“…[11][12][13] The most extensively characterized Toll-like receptor, TLR4, is the receptor for the endotoxin of gram-negative bacteria. 14,15 Previous studies by Cunningham et al 16 demonstrated that endotoxininduced acute renal failure is completely dependent on TLR4 signaling. Likewise, we recently demon-strated that cisplatin and endotoxin exert synergistic renal toxicity that is TLR4-dependent.…”
mentioning
confidence: 98%